Excitatory repetitive Transcranial Magnetic Stimulation applied to the right inferior frontal gyrus has no effect on motor or cognitive impulsivity in healthy adults - Yang, Cheng-Chang; Khalifa, Najat; Völlm, Birgit (Elsevier, 2018)
Background: Impulsivity is a multi-faceted concept. It is a crucial feature of many neuropsychiatric disorders. Three subtypes of impulsivity have been identified: motor, temporal, and cognitive impulsivity. Existing evidence suggests that the right inferior frontal gyrus (rIFG) plays a crucial role in impulsivity, and such a role has been elucidated using inhibitory repetitive transcranial magnetic stimulation (rTMS). There is a dearth of studies using excitatory rTMS at the rIFG, an important gap in the literature this study aimed to address. Methods: Twenty healthy male adults completed a single-blind sham-controlled randomised crossover study aimed at assessing the efficacy of rTMS in the neuromodulation of impulsivity. This involved delivering 10-Hz excitatory rTMS to the rIFG at the intensity of 100% motor threshold with 900 pulses per session. Trait impulsivity was measured at baseline using the Barrett Impulsiveness Scale and UPPS-P Impulsiveness Scale. The Stop Signal Task (SST) and Information Sampling Task (IST), administered before andafter rTMS sessions, were used as behavioural measures of impulsivity. Results: No significant changes on any measures from either SST or IST after active rTMS at the rIFG compared to the sham-controlled condition were found. Conclusions: Excitatory rTMS applied to the rIFG did not have a statistically significant effect on response inhibition and reflective/cognitive impulsivity. Further research is required before drawing firm conclusions. This may involve a larger sample of highly impulsive individuals, a different stimulation site or a different TMS modality such as theta burst stimulation.